Інтерфейс користувача. Особливості розробки інтерфейсу користувача для ігрових застосунків - Ареф’єв, О. О. (ХНУРЕ, 2021)
Every day the modern person interacts with the interface in one way or another, for example using a smartphone to set the alarm clock and wake up on time, weighing goods in a store, using the subway, a bank card and the like. Today it is impossible to imagine life without all this interaction. People just need it besides interfaces make modern life much easier. Despite all this it is still possible to meet a large number of interfaces which will be difficult to use because of its bad design. The main problem quite often arises and unfortunately is widespread - it is cumbersome with a lot of information interface.
Науковий керівник – ст. викл. каф. ПІ Новіков Ю. С.
Keywords: розробки інтерфейсу користувача; ігрові застосунки